Profesionalisme Dokter Dan Kepuasan Pasien Di Rumah Sakit Dan Klinik Di Kota Bandung - Mochammad Reza Hidayat; Hidayat Ahmad; Siko Abdul Majid; Vip Paramarta (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
The COVID-19 pandemic has caused decreased hospital visits in East Java in 2020. This condition is followed by patient satisfaction indices that were under the target in several hospitals in bandung City between 2020-2021. The professionalism of physicians has been an issue among the public as the community accused them of being unprofessional in handling COVID-19. In this observational quantitative study, the correlation between physician professionalism and patient satisfaction was analyzed using a cross-sectional design. The target population was the community in bandung City, East Java, from whom 100 respondents were selected and given online questionnaires from February to March 2022 to gain the relevant data. The data were then statistically analyzed in SmartPLS application. The results of the study showed that the physician professionalism shared a significant relationship with patient satisfaction (p = 0.000). Therefore, physician professionalism should be prioritized by managers to improve the patient satisfaction in hospitals and health clinics.